The Impact of Free Association Among Students: Case Study in Toineke Village, Kualin District, South Central Timor District - Sergi Fatu; Sutrisno Sutrisno; Novida Dwici Yuanri Manik (SERVIRE: Jurnal Penelitian dan Pengabdian, 2022)
This study aims to 1) determine the causes of the emergence of promiscuous behavior in Toineke Village, Kualin District, South Central Timor Regency; 2) Knowing the impact of promiscuity for students in Toineke Village, Kualin District, South Central Timor Regency. This research was conducted in Toineke Village, Kualin District, Nusa Tenggara Regency; The research approach used is a qualitative research approach. Data collection techniques using interview techniques, observation, and documentation. For the technique of determining informants using the Snowballin Sampling technique. The data analysis technique used is interactive model analysis using three stages, namely data reduction, data presentation and conclusion drawing or verification. The results of this study indicate that promiscuity among students in Toineke Village, Kualin sub-district, Timor Tengah Selatan Regency is caused by a cultural shift, which lacks attention from parents, close friends, and the media from these various factors so that it has an impact on decreasing student achievement, dropping out of school and getting pregnant. out of wedlock. Penelitian ini bertujuan untuk 1) Mengetahui penyebab munculnya perilaku pergaulan bebas di Desa Toineke Kecamatan Kualin kabupaten Timor Tengah Selatan; 2) Mengetahui dampak pergaulan bebas bagi pelajar di Desa Toineke Kecamatan Kualin Kabupaten Timor Tengah Selatan. Penelitian ini dilakukan di Desa Toineke Kecamatan Kualin Kabupaten Nusa Tenggara; Pendekatan penelitian yang digunakan yaitu pendekatan penelitian kualititatif. Teknik pengumpulan data dengan menggunakan teknik wawancara, observasi, dan dokumentasi. Untuk teknik penentuan informan menggunakan teknik Snowballin Sampling. Teknik analisis data yang digunakan yaitu analisis model interaktif menggunakan tiga tahapan yaitu reduksi data, penyajian data dan penarikan kesimpulan atau verifikasi. Hasil penelitian ini menunjukkan bahwa pergaulan bebas di kalangan pelajar di Desa Toineke kecamatan Kualin Kabupaten Timor Tengah Selatan disebabkan oleh pergeseran budaya, yang kurangnya perhatian orang tua, teman dekat, dan media dari berbagai faktor tersebut sehingga berdampak pada menurunnya prestasi pelajar, putus sekolah dan hamil di luar nikah.